State-of-the-art review on the design and performance of steel pallet rack connections. (August 2016) - Shah, S.N.R.; Sulong, N.H. Ramli; Jumaat, M.Z.; Shariati, Mahdi
Abstract: Steel pallet racks (SPRs) are used in the industrial buildings, warehouses and superstores for storing a multitude of different kinds of goods. Because of changing needs over the years, it is often desirable that such installations be readily demountable and capable of reassembly. Therefore, the beam-to-column connections (BCCs) used in SPRs are boltless in nature. SPR BCCs govern the stability of the frame in the down-aisle direction. The design of SPR BCCs is one of the problems for designers that cannot be handled routinely within the existing design specifications available for bolted and welded connections. Moreover, the studies on the considerations necessary for the design and performance of SPR BCCs solely are rarely available. It is therefore, essential to bring to light the factors that play significant role to improve the design and performance of SPR BCCs. A critical review of the research performed over the last few decades into the global stability of SPR structures in the down-aisle direction only is presented in this paper. The information about the design methodologies and testing procedures defined in the literature and design codes as well as the factors governing the performance of boltless connections are identified. The major failure modes are highlighted. The characteristics of the main elements constituting SPRs are also succinctly discussed. Based on the findings, the limitations of current study are highlighted and future research areas are identified. Highlights: Studies discussed the SPR BCCs fully and/or partially are reviewed. Increased moment-shear ratio increases the design value of stiffness. Connection fails mainly due to the failure of column, beam end connector and tabs. Design depends on the material and geometry of the beam, column and the connector. Study on fire behavior and component modeling of SPR BCCs should be performed.